Clinical, immunological, and genetic investigations in a rare association of type 1 diabetes with xeroderma pigmentosum - Taieb, Ach; Nacef, Imen; Ghariani, Nadia; Nabli, Nadia; Hasni, Yosra; Kacem, Maha; Chaieb, Molka; Maaroufi, Amel; Denguezli, Mohamed; Ach, Koussay (Pediatric Endocrinology Diabetes and Metabolism, 2022)
Xeroderma pigmentosum (XP) is a rare genodermatosis predisposing to skin cancers. Autoimmune diseases related to XP are rarely discussed in the literature. Type 1 diabetes (T1D) has been associated with other genodermatoses like Cockayne syndrome, but it has never been described in XP. In the present study, we report the rare occurrence of T1D in XP patients. Five XP patients belonging to 4 consanguineous families originating from different regions of Tunisia were investigated. Their ages ranged between 8 and 18 years. All the patients had a severe hypovitaminosis D. All the patients had positive GAD antibody levels, and 4 of them had familial history of other autoimmune diseases. The spectrum of XP was variable in all the patients, with dermatological and neurological symptoms, and the occurrence of some cancers. Various hypotheses have been proposed to explain this association, among of which we cite the role of immunomodulation and down-regulation of ATP-dependent DNA excision repair protein genes, implying that impaired DNA repair may contribute to the development of some autoimmune diseases. Vitamin D3 deficiency secondary to sun protective measures was found in all patients and thus may play a role in increasing T1D risk in these patients.